A contextual analysis of rules governing membership in the Methodist church in Zimbabwe - Mtemasango, James Mhaka (Midlands State University, 2017)
The research focuses on making an evaluation of the rules that govern membership in the Methodist Church in Zimbabwe, in light of the changes in the current Zimbabwean context. The nature and identity of the MCZ is characterized by the rules that moderate the social and religious life of its membership. The crafting of the rules has been largely affected by the social, economic, political and religious challenges in the society the MCZ is ministering to. The social environment in Zimbabwe has seen a radical change as we turned into the 21st century calling on the church to reform its rules to ensure it adequately responds to the challenges being faced by the society. In an environment characterized by religious competition the MCZ is challenged to reform its rules so that it responds to the social and religious aspiration of the society to ensure that it remains relevant to the environment and position itself as a church of choice. The research is focusing on bringing proposals that could help transform the rules guiding and the conduct of the MCZ to ensure the church continue to attract new members in this time and age.